The Impact of Ramadan on the Income of Micro, Small, and Medium Enterprises (MSMEs) in Batang Kuis District - Rizky Prayuda; Syamsul Effendi; Abdul Rahman (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study analyzes the impact of the Ramadan month on the income of Micro, Small, and Medium Enterprises in Batang Kuis District. The research employs a quantitative approach using surveys and interviews with MSME actors to compare their income before, during, and after Ramadan. The results reveal a significant increase in MSME income by approximately 63.4% during Ramadan, driven by shifts in consumption patterns, increased demand for Ramadan-specific products, and strategic business adaptations such as product diversification and adjusted operating hours. The study also discusses the challenges faced by MSMEs, including limited capital and digital marketing access, which affect their ability to fully optimize income growth during this period. The findings suggest that Ramadan serves as a critical opportunity for MSMEs to enhance their economic performance, provided they implement effective strategies and receive adequate support.